A relação entre o envolvimento religioso materno e a mortalidade na infância na Região Nordeste em 2010 - Souza, Mayany Cleyses Morais de (2018)
The present study highlighted maternal religious affiliation as an important factor associated with infant mortality. The main objective of this study was to analyze the relationship between infant mortality and maternal religious affiliation categories for the Northeast Region in 2010. In Brazil, infant and child mortality rates are declining considerably (SZWARCWALD & CASTILHO, 1995; GARCIA & SANTANA, 2011; TEIXEIRA et al, 2016). In addition, the country has undergone significant demographic, economic, social, environmental and cultural transformations, among which, changes in the religious field are also observed (ALVES, CAVENAGHI & BARROS, 2014). In order to reach the proposed objectives, this study used as a source Demographic Census 2010 database that provides details on religious affiliation, as well as data on infant and child mortality and several of its associated factors. To reach the proposed objectives, three Poisson regression models with robust variance were applied for infant and child mortality: Model 1 included only the associated factor of interest in this dissertation (maternal religious affiliation). Maternal demographic characteristics (age, color / race, parity and marital status) were added in Model 2, and in Model 3, the economic characteristics of the mother and household were added (levels of schooling, urban/rural household, type of sewage, the existence of piped water in the residence and if someone in the household received benefits from social programs). Among the main results obtained, it is highlighted that maternal religious affiliation was not associated with infant mortality. In the case of child mortality, maternal religion reached statistical significance in Model 1, in which the 'traditional evangelical' (RR = 0.76, p <0.05) and 'Pentecostals evangelical' (RR = 0.80; p <0.05) showed protective effects. In Model 2, the category 'traditional evangelical' lost statistical significance, but the group of Pentecostal mothers not only maintained a statistically significant association, but also increased its protective effect (RR = 0.84, p <0.05). Others results showed deleterious effects of maternal age’s extremes: '10 to 19 years '(RR = 1.38, p <0.05) and '35 years or more' (RR = 1.33, p <0.05). Also, parity equal three or more children (RR = 1.39, p <0.05), being widowed (RR = 1.64, p <0.10) and residing at home with adequate sanitary sewage (RR= 0.73, p <0.05). In general, the results found for religious affiliation partially corroborate the Wood, Williams & Chijiwa (2007) hypothesis that, over time, Pentecostal mothers would reach the level of traditional Protestant mothers in terms of death protection in childhood.